Role of Ultrasonography with Color Doppler in the Evaluation of Acute Scrotal Pain at a Tertiary Care Centre in Eastern Nepal - Shah, Arbindra; Shah, Amit Kumar; Rimal, Rajesh; Shrestha, Manmohan Bir; Baskota, Bashu Dev (Medical Journal of Eastern Nepal, 2026)
Background Acute scrotal pain is a common urological emergency requiring prompt assessment to prevent testicular loss. Etiologies include surgical conditions such as testicular torsion and medical conditions like epididymo-orchitis. Clinical differentiation is often challenging, and delayed or misdiagnosis can lead to irreversible testicular damage. Ultrasonography with color Doppler plays a key role by evaluating both the morphology and vascularity of the testicle. Objectives To determine the diagnostic role of ultrasonography with color Doppler in the evaluation of acute scrotal pain and to identify its etiological spectrum in Eastern Nepal. Methods A prospective observational study was conducted among 118 male patients with acute scrotum pain of less than 72 hours’ duration, recruited from the emergency department of Hospital at B & C Medical College Teaching Hospital and Research Center. Patients underwent grey-scale and color Doppler ultrasonography, and findings were correlated with surgical or clinical outcomes. Data was analyzed using IBM ’SPSS’ Statistics v.27. Continuous variables were presented as mean ± SD, and categorical variables were analyzed by the Chi-square test. A p-value < 0.05 was considered to be significant. Results The mean age was 22.97 ± 6.87 years, and the mean duration of symptoms was 18.54 ± 10.01 hours. The most common etiologies were epididymitis (33.1%), epididymo-orchitis (20.3%), and testicular torsion (15.3%). Increased flow (61.0%) and absent/reduced flow (15.3%) were the predominant Doppler patterns. Conclusions Color Doppler ultrasonography is a rapid, non-invasive, and highly reliable diagnostic tool for differentiating testicular torsion from inflammatory causes, thereby improving management outcomes and testicular salvage rates in acute scrotal pain.